Using the electrodermal activity signal and machine learning for diagnosing sleep - Piccini, Jacopo; August, Elias; Óskarsdóttir, María; Arnardóttir, Erna Sif (Frontiers in Sleep, 2023)
The use of the electrodermal activity (EDA) signal for health diagnostics is becoming increasingly popular. The increase is due to advances in computational methods such as machine learning and the availability of wearable devices capable of better measuring EDA signals. One field where work on EDA has significantly increased is sleep research, as changes in EDA are related to different aspects of sleep and sleep health such as sleep stages and sleep-disordered breathing; for example, obstructive sleep apnoea (OSA). In this work, we used supervised machine learning, particularly the extreme gradient boosting (XGBoost) algorithm, to develop models for detecting sleep stages and OSA. By complementing a standard generic statistical feature set with EDA-specific variables, we obtained an average macro F1-score of 57.5% and 66.6%, depending on whether we considered five or four sleep stages, respectively. When detecting OSA, regardless of the severity, the model reached an accuracy of 83.7% or 78.4%, depending on the measure used to classify the participant’s sleep health status. The research work presented here provides further evidence that, in the future, most sleep health diagnostics might well do without complete PSGs studies, as wearables can detect well the EDA signal.